Die "Confessiones" Augustins: ein autobiographisches Projekt in der Spätantike - Löhr, Winrich Alfried (Römische Quartalschrift für christliche Altertumskunde und Kirchengeschichte, 2019)
"The Confessions of Augustin: an autobiographical project of late antiquity" - The article asks what makes possible Augustin’s autobiographical writing and self-reflection in the Confessions, and shows how Augustin writes about himself and his environment in such a way that they become transparent as a document of conversion to a life with God and to truth: Arriving at this truth implies self-knowledge and knowledge of God and means that Augustin has attained the beatitudo possible on earth through his conversion. The Confessions claim unreserved transparency, appeal to the caritas of the readers and want to make possible their conversion to similar self-knowledge and knowledge of God. The self-transparency of the autobiographical subject implies a claim for the authenticity of that which is communicated. Special attention is paid to the implicit and explicit psychology of the Confessions, which adopts and modifies concepts from the Stoa and Neoplatonism. Augustin tries out various literary methods and techniques to achieve maximum effect on his audience and in this way produces a text about which he confidently tells his readers almost thirty years later that it retains the power of converting the human spirit and affect to God (retr. 2,6).